2016
DOI: 10.2298/fil1609599b
|View full text |Cite
|
Sign up to set email alerts
|

On the hyperbolicity of edge-chordal and path-chordal graphs

Abstract: If X is a geodesic metric space and x 1 , x 2 , x 3 ∈ X, a geodesic triangle T = {x 1 , x 2 , x 3 } is the union of the three geodesics [x 1 x 2 ], [x 2 x 3 ] and [x 3 x 1 ] in X. The space X is δ-hyperbolic (in the Gromov sense) if any side of T is contained in a δ-neighborhood of the union of the other two sides, for every geodesic triangle T in X. An important problem in the study of hyperbolic graphs is to relate the hyperbolicity with some classical properties in graph theory. In this paper we find a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The papers [11,52,5,13] prove, respectively, that chordal, k-chordal, edge-chordal and join graphs are hyperbolic. Moreover, in [5] it is shown that hyperbolic graphs are path-chordal graphs. These results relating chordality and hyperbolicity are improved in [34].…”
Section: Introductionmentioning
confidence: 99%
“…The papers [11,52,5,13] prove, respectively, that chordal, k-chordal, edge-chordal and join graphs are hyperbolic. Moreover, in [5] it is shown that hyperbolic graphs are path-chordal graphs. These results relating chordality and hyperbolicity are improved in [34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a way to approach the problem is to study hyperbolicity for particular types of graphs. In this line, many researches have studied the hyperbolicity of several classes of graphs: chordal graphs [7,14,40,54], vertex-symmetric graphs [15], bipartite and intersection graphs [22], bridged graphs [37], expanders [39] and some products of graphs: Cartesian product [41], strong product [16], corona and join product [17].…”
Section: Introductionmentioning
confidence: 99%
“…They prove that k-chordal graphs are hyperbolic where a graph is k-chordal if every induced cycle has at most k edges. In [1], the authors define the more general properties of being (k, m)-edge-chordal and (k, k 2 )-path-chordal and prove that every (k, m)-edge-chordal graph is hyperbolic and that every hyperbolic graph is (k, k 2 )-path-chordal. In [32], we continue this work and define being ε-densely (k, m)-path-chordal and ε-densely k-path-chordal.…”
Section: Introductionmentioning
confidence: 99%
“…In [32], we continue this work and define being ε-densely (k, m)-path-chordal and ε-densely k-path-chordal. In [1] and [32], edges where aloud to have any finite length but in this work we assume that all edges have length one. Therefore, the distinction between edge and path is unnecessary and these properties are referred as (k, m)-chordal and ε-densely k-chordal.…”
Section: Introductionmentioning
confidence: 99%